Determine the Appropriate Forecasting Method and Inventory Model in Tang Company - Margono, Steven; Lestari, Yuliani Dwi (Journal of Business and Management, 2015)
Abstract. Purpose – The purpose of this paper is to give recommendation in terms of inventory management to Tang Company. So that, production is on time and in the right amount (avoid overstock, shortage). Methodology / Approach – The methodology used for the research is interviewing company’s Director and Secretary and collecting company’s purchasing and sales data to get company’s business and product data. After that, company’s type of demand is identified and a new inventory model which suits with the demand characteristic is proposed. Current company’s inventory management system is also analyzed and compared with proposed inventory model to see whether the new inventory model gives more benefit to the company. Finally, recommendations will be given to the company with how to implement it to their system and daily operation. Findings – Tang Company’s demand and lead time are variable, so probabilistic model is used to determine the safety stock and reorder point. EOQ model is used to maximize order quantity, while Material Requirements Planning technique is used to calculate total cost for proposed inventory management. After both existing and proposed inventory management results are compared, it seems that the company can save a large number of money by implementing the new inventory model. Research Limitation – The limitation of the research is types and colors of material and final product, which are bur polyester benhur, donker, and black; and purchasing data and sales data, which are from 1st January 2014 until 31st December 2014. Keywords: Inventory Management, Economic Order Quantity, Probabilistic Model, Material Requirements Planning, Textile Industry.